2018
DOI: 10.1021/acs.cgd.8b01567
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Frameworks Constructed from Group 1 Metals (Li, Na) and Silicon-Centered Linkers

Abstract: A series of 'light metal' MOFs containing SBUs based on Li + and Na + cations have been prepared using the silicon-centered linkers MexSi(p-C6H4CO2H)4-x (x = 2, 1, 0). The unipositive charge, small size, and oxophilic nature of the metal cations gives rise to some unusual and unique secondary building units (SBUs), including a 3D nodal structure built from sodium and oxygen ions when using the triacid linker (x = 1). The same linker with Li + cations generated a chiral, helical SBU, formed from achiral startin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…In 2019, Davies et al 42 reported a series of 1D MOFs based on Li + and Na + metal centers using silane-based organic linkers. For example, the 1D Li-MOF [IMP-24Li, Li 4 L1$DMF, in which L1 ¼ 4,4 0 ,4''-(methylsilanetriyl)tribenzoate] was synthesized by mixing lithium nitrate (LiNO 3 ) and H 3 L1 in DMF at the reaction temperature of 170 C. IMP-24Li crystallized in a unique chiral space group of P3 1 21, wherein each unit cell contained one L1 ligand, four lithium cations, and one coordination DMF molecule.…”
Section: Isbu Mofs Constituted Of Metal(i) Central Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2019, Davies et al 42 reported a series of 1D MOFs based on Li + and Na + metal centers using silane-based organic linkers. For example, the 1D Li-MOF [IMP-24Li, Li 4 L1$DMF, in which L1 ¼ 4,4 0 ,4''-(methylsilanetriyl)tribenzoate] was synthesized by mixing lithium nitrate (LiNO 3 ) and H 3 L1 in DMF at the reaction temperature of 170 C. IMP-24Li crystallized in a unique chiral space group of P3 1 21, wherein each unit cell contained one L1 ligand, four lithium cations, and one coordination DMF molecule.…”
Section: Isbu Mofs Constituted Of Metal(i) Central Ionsmentioning
confidence: 99%
“…Apart from the common Li + -and Na + -based ISBU MOF examples, 42,46,47 heavier alkaline cations like K + and Rb + have also been utilized for ISBU MOF constructions. 44 A redox tetracarboxylic acid H 4 (TTF-TC) (Fig.…”
Section: Isbu Mofs Constituted Of Metal(i) Central Ionsmentioning
confidence: 99%
“…Other groups have also been interested in lightweight networks and demonstrated the ability of metals ions such as Li + to serve as centres within ionic networks. 4–13…”
Section: Introductionmentioning
confidence: 99%
“…Functionalization of these building blocks in the 4‐position of the phenyl rings gives molecules with divergent functionality, which is ideal for framework formation. Unsurprisingly, a range of metal organic frameworks (MOFs) [1–12] hydrogen‐bonded organic frameworks (HOFs), [13–22] covalent organic frameworks (COFs), [23, 24] and other covalently‐bonded porous materials [25–28] have been prepared from these tectons. Tetraphenylsilane derivatives are typically significantly easier to synthesize [29] than their tetraphenylmethane analogues and so would appear to be attractive candidates for framework assembly, although it is not necessarily true that the building blocks are interchangeable.…”
Section: Introductionmentioning
confidence: 99%